Herbal Recipes, Drug Indications and Sustainability Potential of Traditional Oral Liquid Formulations in Ogbomoso, Nigeria (Global Journal of Science Frontier Research, 2021)
Confirmation of identity, along with determination of the quality and purity of herbal drug is an important step towards ensuring its safety and efficacy. This study therefore sought to document the botanical constituents and drug indications of traditional oral liquid herbal formulations (TOLHFs) manufactured in Ogbomoso, Nigeria. It also examined the conservation status of the medicinal plants so used alongside the cultivation efforts being made by the drug manufacturers in order to provide information on whether continual exploitation of the plants for TOLHFs is sustainable. Through a questionnaire, 14 traditional herbal medical practitioners (THMPs) provided information on the recipes of their products, the sources of their raw material herbs, and types of health conditions treated or managed with the drugs. Sustainability potential of the drugs was quantified as relative percentage of the three choices of sources of raw material herbs available to the manufacturers in conjunction with the conservation status of the plant species as recorded by the International Union for Conservation of Nature (IUCN).Fifty-seven medicinal plant species (in 34 angiosperm families) were used to formulate 71 herbal recipes that are indicated for treating 14 different health conditions.
Keywords: medicinal plants; traditional oral liquid herbal formulations; sustainable exploitation of medicinal herbs